Mechanism underlying rapid responses to boron deprivation in Arabidopsis roots. Issue 1 (2nd January 2018) - Kobayashi, Masaru; Miyamoto, Maako; Matoh, Toru; Kitajima, Sakihito; Hanano, Shigeru; Sumerta, I Nyoman; Narise, Takafumi; Suzuki, Hideyuki; Sakurai, Nozomu; Shibata, Daisuke
ABSTRACT: Transferring hydroponically grown Arabidopsis plants ( Arabidopsis thaliana L.) to boron (B)-free medium kills the cells in root tips within an hour. To understand the mechanism underlying the induced rapid cell death, the Arabidopsis response to B deprivation was characterized using inhibitors of presumably involved cellular processes. The results suggest that stretching of the plasma membrane and the influx of calcium ions through mechanosensitive channels triggered the responses and that reactive oxygen species were overproduced under B-deprived condition. In addition, nitric oxide was observed to be involved in cell death, suggesting that Arabidopsis root cells undergo programmed cell death upon B deprivation. RNA sequencing analysis revealed that B deprivation induced transcriptome changes that resembled pathogen-induced responses. In summary, we speculate that B deprivation induces hypersensitive responses in Arabidopsis roots as a response to defective cell wall structures.